An annotated type catalogue of the anguid, dibamid, scincid and varanid lizards in the Department of Herpetology, Zoological Institute, Russian Academy of Sciences, St. Petersburg, Russia (Reptilia: Sauria: Anguidae, Dibamidae, Scincidae and Varanidae) - Barabanov, Andrei; Milto, Konstantin (Zootaxa, 2017)
A complete catalogue is provided for the type specimens of anguid, dibamid, scincid and varanid lizards in the herpetological collection of the Zoological Institute, Russian Academy of Sciences, St. Petersburg, Russia (ZISP), as of January 2017. The collection contains a total of 170 type specimens, representing 50 taxa in the four lizard families under consideration. Thirty-one of these taxa are regarded currently as valid. The types of four taxa (one holotype, one lectotype and two paralectotypes) could not be located in the ZISP collections in January 2017. A majority of the types are skinks (43 taxa, 155 types), many of which were described by the late Ilya Darevsky (1924–2009).